Logistical outsourcing as an effective enterprise activity mechanism rising - Tkach, Oleg; Hryniv, Liubov; Mykhailiv, Halyna (Journal of Vasyl Stefanyk Precarpathian National University, 2020)
The purpose of the article is to substantiate logistics outsourcing as an effective mechanism for improving the efficiency of the enterprise. The authors summarize the arguments and counterarguments in the scientific discussion on logistics outsourcing as one of the best methods of optimizing resources in the activity of enterprises, one of the important factors of modern business. Systematization of the results of the research of scientific sources made it possible to identify the problems of outsourcing use in various spheres of activity of economic entities. Systematization of studies of aspects of enterprise management based on logistic approaches has allowed formulating the statement that special value all over the world in logistics is devoted to outsourcing. For many years there is a tendency in this area to transfer a part or all of the logistics functions to specialized companies and outsourcing of logistics services is used by the vast majority of enterprises. Because, as higher the level of consumption in the country, there is more need to involve in the supply chain the goods of qualified logistics operators and transfer part of their operations to logistics outsourcing. The authors estimate the logistic outsourcing of the enterprise of PE “VEGA LTD” for the method of Yu. Zhelinskiy, which combines the change of income and expenses of the enterprise. Based on the calculations, it is proved that outsourcing for PE “VEGA LTD” is profitable. Therefore, it is advisable to use outsourced services not only for transport logistics but also for other logistic activities of the enterprise. In the process of investigating the problems of logistics outsourcing and its impact on the efficiency of foreign economic activity of the company, the authors proved that outsourcing in logistics is one of the most modern business models. The use of this approach makes it possible to achieve significant competitive advantages in the activity of the enterprise. The main motives that drive outsourcing of logistics functions are the desire to make the business manageable, reduce transaction costs while obtaining quality service and profit. The results of the study are of practical importance and may be useful to scholars interested in the study of logistical outsourcing, as well as to the enterprises where outsourcing is most commonly used.